Governing for and through harmonious community: The emergence of moral clinics in China. (August 2021) - Zhang, Shaoying; McGhee, Derek
In this article, we advocate the adoption of 'more temporal and processual characters' to understand contemporary community governance in China. We show that communities in China are seen both as producing moral problems and as being the solutions to these problems. Furthermore, we argue that the establishment of the moral clinic provides an alternative to neoliberal ways of self-governance. In the article, we present moral clinics as a new form of community self-governance whose aim is to achieve a complex balance between various conflicts in the context of China's unprecedented urbanisation in the name of governing for and through community harmony. Through examining the establishment of moral clinics, we expose how the relationship between the moral 'hospitalisation' of society and the socialisation of individuals can be understood in new ways. We argue that the institutionalisation of this 'moral work' is a strategy based on old techniques of Chinese traditional medicine that are being enhanced by modern organisational settings. In addition, we examine the micropolitics of the moral clinic through exposing the power relations behind its structural design, and especially its links with the state.